Newborn Hearing Screening in a Public Maternity Ward in Curitiba, Brazil: Determining Factors for Not Retesting - Luz, Idalina; Ribas, Angela; Kozlowski, Lorena; Willig, Mariluci; Berberian, Ana Paula (International Archives of Otorhinolaryngology, 2016)
Introduction Law 12.303/10 requires hearing screening in newborns before hospital discharge to detect possible hearing problems within the first three months after birth. If the newborn fails the test or presents signs of risk for hearing loss, it must undergo a retest and monitoring during the first year of life. In practice, this often does not happen.Objective To identify, in a group of mothers of children with risk factors for hearing loss, the determining reasons for non-compliance with the auditory retest. Method This is a cross-sectional quantitative study. For data collection, we handed a semi-structured questionnaire to 60 mothers of babies at risk for hearing loss who did not attend the hearing retest after hospital discharge. The questionnaire investigated their age, education, marital status, level of knowledge about the hearing screening, and reasons for non-compliance with the retest. We compared and analyzed data using the Chi-square test at a significance level of 0.05%.Results Our study found that 63% of the respondents were unaware of the hearing screening and most did not receive guidance on testing during prenatal care; 30% of participants stated forgetting as the reason for not attending the retest. There was no significant relationship between age, education, and marital status regarding knowledge about the test and the non-compliance with the retest.Conclusion Identified as the most significant determining factors for non-compliance with the newborn hearing screening retest were the surveyed mothers' forgetting the date, and their ignorance as to the importance of retesting.
Keywords: hearing; deafness; speech-language pathology; pediatric nursing